Kajian Sastra Feminisme terhadap Citra Perempuan Adonara dan Ketidakadilan Gender dalam Novel “Ikhtiar Cinta dari Adonara” Karya J. S. Maulana - Yunita Laka Marawali (Jurnal Edukasi Sumba (JES), 2020)
This study aims to describe the image of Adonara women and the types of gender injustice experienced by female characters in the novel "Ikhtiar Cinta dari Adonara" by J. S. Maulana. This study uses a literary approach based on literary studies of feminism and gender. The object of research is the description of Adonara women and gender injustice found in the novel "Ikhtiar Cinta dari Adonara" by J. S. Maulana. The source of data in this study is the novel “Ikhtiar Cinta Adonara’ by J. S Maulana. The novel written by J. S. Maulana consists of 320 pages. Published by Kaysa Media (Puspa Swara Group) in 2014. The data analysis technique was done by reducing data, presenting data analysis and interpreting the data and summarizing the results of research in order to obtain a picture of the image of women in the novel "Ikhtiar Cinta dari Adonara" by J. S. Maulana. In this study, researchers analyzed two female figures to describe the image of women in the novel. The results obtained are (a) The image of a woman, namely the figure of Syarifah, is a Muslim who is devout in worship and always submits to God, a woman who is educated, tough, has positive thoughts, is courageous and principled, is humble, and a woman who loves sincerely. (b) Fatimah's self-image, namely women who are willing to sacrifice, are brave and have principles, (c) gender injustice is found, namely marginalization, subordination, stereotypes, violence, and workload.